Morphological and Functional Evaluation of Oral Citicoline Therapy in Chronic Open-Angle Glaucoma Patients: A Pilot Study With a 2-Year Follow-Up - Michele Lanza; Ugo Antonello Gironi Carnevale; Luigi Mele; Mario Bifani Sconocchia; Silvia Bartollino; Ciro Costagliola (Frontiers Media S.A., 2019)
Aims: To study the neuroprotective effect of oral citicoline (CT) therapy in primary open-angle glaucoma (POAG).Methods: This study included one eye each of 60 POAG patients. Patients were randomly divided into two groups (A and B) of 30 participants each. Only patients of group A were administered with CT therapy. Age, sex, and disease duration were matched between groups. Despite a stable intraocular pressure (IOP), a slow disease progression-assessed by standard automated white-on-white perimetry (SAP) in the previous 3 years-occurred in all patients. All patients underwent a complete eye examination, including IOP measurement, SAP, retinal nerve fiber layer (RNFL) thickness, and ganglion cell complex (GCC) thickness measurements with optical coherence tomography (OCT), before starting CT treatment and at 6, 12, 18, and 24 months' follow-up. Parameter differences between groups were evaluated at each eye check.Results: After 18 months, mean values of SAP mean deviation (MD) of group A were significantly (p = 0.039) higher (−7.25 db) than those of group B (−8.64 db). Moreover, they appeared stable in the following visits, whereas in group B, mean MD values continued to significantly (p < 0.001) decrease (−9.28 db) over time. Mean RNFL and GCC thickness in group A were significantly (p < 0.01) higher (70.39 and 71.19 μm, respectively) than in group B (64.91 and 65.60 μm, respectively) after 12 months of CT therapy. Furthermore, they appeared to be stable over the later visits, whereas they thinned significantly (p < 0.001) over time in group B.Conclusion: These findings suggest that CT therapy seems to be effective in slowing POAG progression. Further studies on a larger population and with a longer follow-up are needed to confirm this pilot investigation.